Efektivitas Penerapan Sistem Informasi Keuangan Daerah (SIKD) di Aplikasi Sistem Informasi Pemerintahan Daerah (SIPD) pada Kecamatan Purworejo Kota Pasuruan - Lazuardi, Andoni; Gunarianto, Gunarianto; Pawestri, Hartini Prasetyaning (Politeknik Negeri Ambon, 2024)
The development of information and communication technology in society provides opportunities for the government to innovate in the development of state apparatus through the implementation of an Electronic-Based Government System (SPBE). SPBE or what is usually called e-government is government administration that utilizes information and communication technology to provide services to government agencies, state civil servant, business people, the community and other parties. A National Regional Financial Information System (SIKD) is needed to provide comprehensive regional financial information to the wider community as well as a basis for fiscal policy-making officials in making decision. This is a form of government responsibility for all development results. SIPD is a form of system created as a form of technology that is utilized and realized. SIPD was designed by the ministry of home affairs with the aim of justifying the flow stages structuring regional plan documents in accordance with requirement of statutory regulations. Keywords: SPBE, SIKD, SIPD, District, Village